Smart Grids Data Management: A Case for Cassandra - Pinheiro, Gil (2021)
The objective of this paper is to present a SMACK based platform for microgrids data storage and management. The platform is being used in a real microgrid, with an infrastructure that monitors and controls 3 buildings within the GECAD - ISEP/IPP campus, while, at the same time, receives and manages data sources coming from different types of buildings from associated partners, to whom intelligent services are being provided. Microgrid data comes in different formats, different rates and with an increasing volume, as the microgrid itself covers more customers and areas. Based on the atual available computational resources, a Big Data platform based on the SMACK stack was implemented and is presented. The Cassandra component of the stack has evolved. AC version 2 is still supported until the version 4 release, and is often still used in production environments. However, a new stable version, version 3, introduces major optimizations in the storage that bring disk space savings. The main focus of this work is on the Data Storage and the formalization of the data mapping in Cassandra version 3, which is contextualized by means of a short example with data coming from the monitoring infrastructure of the microgrid.